The Impact of Effectiveness of Board Commissioner, Audit Committee, Managerial Ownership, and Institutional Ownership on the Corporate Social Responsibility - Alya Sabilita Asahra; David Pesudo (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2023)
The Covid-19 pandemic has had a profound global impact since its emergence in 2019. In Indonesia, numerous companies have faced significant challenges as a result. Despite the adverse effects, many companies have managed to survive and continue their operations. However, the pandemic has posed new challenges for corporate social responsibility (CSR) initiatives, which play a crucial role in addressing societal needs. This study aims to empirically examine the effect of the effectiveness of the board of commissioner, audit committee, managerial ownership, and institutional ownership on corporate social responsibility. This analysis uses independent variables, namely the board of commissioners, audit committee, managerial ownership, and institutional ownership. The dependent variable is corporate social responsibility. This study uses annual reports from food and beverage companies listed on the IDX that carry out corporate social responsibility between 2019 and 2021. Sampling uses purposive sampling using criteria samples. Based on the criteria determined to select the sample, the number of samples was 22 companies. The statistical method uses multiple linear regression analysis. The result of developing the hypothesis that the board of commissioners has a significant effect on corporate social responsibility. Meanwhile, the audit committee, managerial ownership, and institutional ownership have no significant effect on corporate social responsibility.